Core-body temperature acquisition tools for long-term monitoring and analysis - Caldeira, J.M.L.P. (2013)
Submitted by João Caldeira (jcaldeira@ipcb.pt) on 2012-09-11T15:37:08Z No. of bitstreams: 1 lifsci_v2_n34_2010.pdf: 1538957 bytes, checksum: 80331f886fe7bba2ed5845a48b53fe99 (MD5)